A "nova" direita brasileira: um estudo do mercado político no pós-impeachment - Vieira, Aiane de Oliveira (2021)
Brazil registered between the implementation of the Real Plan in 1994 and 2012 significative results in all its socioeconomic indexes. The country seemed to be going toward modernization, cultural change, the consolidation of its democratic system as well as human empowerment. This path, nonetheless, was interrupted and since 2013 the country has faced political, social, cultural, economic and institutional crises, which not only damaged the image of the government and its political institutions, but also stimulated the emergence of political groups that identify themselves with what the literature has called an “extreme” or a “new” right. The reasons that promoted the emergence of this radical right worldwide and, more specifically in Brazil, are multiple and evolve economic, political and cultural issues. To understand this phenomenon, it is necessary to look into the various actors involved in this dynamic: voters (demand), political elites (supply) and the media, more specifically, social media as an intermediary between demand and supply. That said, we aim to identify the profile of those voters who support the “new” right’s rhetoric, expressed mostly on Jair Bolsonaro, based on socioeconomic and demographic elements; and cultural values such as authoritarianism, law and order, tradition and stability, nationalism and intolerance to groups considered minorities. Second, we want to comprehend the dynamics of the use of social media in the political scene. We aim to understand how they may have contributed to shape voters’ values and perceptions. Thus, our research question is: Who is the Brazilian “new” right and how it built itself through social media? Our hypothesis is that Bolsonaro’s voters are more inclined to cultivate attitudes aligned with those other extreme right movements worldwide. Additionally, we believe those attitudes are reinforced among those who consume more online content. In order to achieve our goals, we use the 2018/2019 America’s Barometer survey data base. Firstly, we build a digital activism index and identify the share of the electorate that identifies with the political figure of Jair Bolsonaro. Secondly, we build four models to measure behavior considered authoritarian, such as: supporting coups when there is too much crime as well as corruption and supporting the closure of the National Congress and the Supreme Court. Lastly, we analyze the relationship among the use of social media, vote in Jair Bolsonaro and authoritarian behavior. The results show that Bolsonaro’s voters are more inclined to cultivate authoritarian behavior and, those who are more active on social media seem to present even stronger authoritarian characteristics.